2022
DOI: 10.1371/journal.pone.0258838
|View full text |Cite
|
Sign up to set email alerts
|

LysM receptors in Coffea arabica: Identification, characterization, and gene expression in response to Hemileia vastatrix

Abstract: Pathogen‐associated molecular patterns (PAMPs) are recognized by pattern recognition receptors (PRRs) localized on the host plasma membrane. These receptors activate a broad-spectrum and durable defense, which are desired characteristics for disease resistance in plant breeding programs. In this study, candidate sequences for PRRs with lysin motifs (LysM) were investigated in the Coffea arabica genome. For this, approaches based on the principle of sequence similarity, conservation of motifs and domains, phylo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 83 publications
(167 reference statements)
0
4
0
Order By: Relevance
“…However, these PRRs, together with some other PRR genes such as FaLysM2 , FaLysM5 , FaLysM7 , FaLysM8 , FaLysM12 , and FaLysM14 , were downregulated at the late stage of infection. A recent study also showed the elevated expression levels of candidate LysM genes at 6 to 24 hpi, followed by a decrease at 48 hpi, in Coffea arabica infected with Hemileia vastatrix ( Santos et al., 2022 ). These results describe that most PRR genes exhibit an initial stimulus with subsequent suppression upon fungus infection.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…However, these PRRs, together with some other PRR genes such as FaLysM2 , FaLysM5 , FaLysM7 , FaLysM8 , FaLysM12 , and FaLysM14 , were downregulated at the late stage of infection. A recent study also showed the elevated expression levels of candidate LysM genes at 6 to 24 hpi, followed by a decrease at 48 hpi, in Coffea arabica infected with Hemileia vastatrix ( Santos et al., 2022 ). These results describe that most PRR genes exhibit an initial stimulus with subsequent suppression upon fungus infection.…”
Section: Discussionmentioning
confidence: 88%
“…A similar function was also proved for Magnaporthe oryzae Slp1 and Mycosphaerella graminicola Mg3LysM ( Marshall et al., 2011 ; Mentlak et al., 2012 ). The inhibition of PRR expression may be associated with the suppression of PTI signaling ( Santos et al., 2022 ). From our transcriptome data, we chose the significantly upregulated LysM effector gene CfLysM2 during C .…”
Section: Discussionmentioning
confidence: 99%
“…Resistance Gene Analog(s) (RGA) sequences to distinguish between resistant and susceptible Arabica coffee plants to H. vastatrix based on presence or absence of PCR product (Alvarenga et al, 2011). A number of studies on mechanism of coffee plants resistance against CLR disease primarily have focused on Arabica and Robusta (Cao et al, 2013;Pestana et al, 2015;Jibat, 2020;Santos et al, 2022;Silva et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Pathogen recognition by cell-surface pattern recognition receptors (PRRs) is the earliest response event of a plant host that initially induces defense mechanisms to inhibit the pathogen invasion. Studies in rice [13] and coffee [14] revealed that plants could promptly recognize fungal infection and activate defense activities through the early expressions of the PRRs before a full development of fungal appressorium around 5-6 h after inoculation. In chili anthracnose, the causal pathogen Colletotrichum was demonstrated to produce appressoria as early as 6 h after inoculation [15].…”
Section: Introductionmentioning
confidence: 99%